Peran Posyandu Remaja Terhadap Perilaku Kesehatan Reproduksi Kesehatan Remaja di Dusun Iroyudan, Kalurahan Guwosari, Kecamatan Pajangan, Bantul - Debby Vitara; Dena Munarsih; Husnul Khatimah; Haka R Pratama; Aditya Mandala Pratama; Bismi Ratu Fortuna Nawawi; Astin Eka Wardani; Apriza Dwi Yanhari; Masbani Ajeng Lestari; Muhammad Fakhrurrozi; Milati Nurul Maulida; Novi Silvianita; Ratih Ratih; Siti Zahro; Rizal Fauzi; Nurul Kusumawardani; Ruwet Rusiyono; Muh. Mustakim (Bangun Desa: Jurnal Pengabdian Masyarakat, 2023)
Youth Posyandu is a public health effort that is managed with the aim of organizing to improve health and healthy life skills in adolescents. The establishment of Youth Poyandu aims to be a forum for improving adolescent reproductive health and increasing adolescent health needs. Based on previous implementation studies, some teenagers do not know anything about reproductive health, such as the risk of menstruation and irresponsible sexual activity. Youth Posyandu is optimal, it is not done. Thus, the Youth Posyandu was formed in Guwosari Hamlet, Iroyudan Village, Pajangan District. In practice, Poyandu youth leaders are selected through a deliberation process. From the results of the formation of the youth Posyandu, it is known that there are two posyandu administrators, namely six youth cadres who later became an extension of their duties under the supervision of the Iroyudan Health Center. According to the agreement, the Posyandu will be held every three weeks. The activity began with the provision of counseling for the Youth Posyandu and disseminated in the first activity the counseling material for the Youth Posyandu on adolescent reproductive health. It is hoped that the establishment of the youth Posyandu can improve adolescent health and increase knowledge about adolescent reproductive health.Keywords: youth posyandu, adolescent reproductive health, youth cadres